Pengembangan Sistem Survey Pembelajaran Berbasis Web Untuk Efisiensi Dan Evaluasi Kualitas Pembelajaran Dengan Metode Prototype - Syaliman, Khairul Umam; Disa Putri, Tiara Ayu; Sapriadi, Sapriadi; Surya, Ibnu; Dwi Putra, Nanda (Politeknik Caltex Riau, 2024)
Madrasah Aliyah Negeri 2 Pekanbaru (MAN 2 Pekanbaru) is one of the Madrasah Aliyah in Pekanbaru. In 2014, MAN 2 Pekanbaru conducted a learning quality survey that was filled in by students. The survey was conducted by distributing paper to students containing questions about learning during one semester. However, there are several obstacles in the survey process, namely the use of excess paper, inefficient time and requires special storage space to store the collected survey paper. These obstacles cause the survey filling process to not run effectively. To overcome these problems, a website for filling out surveys on the quality of learning in schools can be built. On this website there are three access roles, namely, students, teachers and academic fields. Making this survey website will use the prototype method. By using this method, users will be directly involved in the analysis and design process. The results of system testing using Black Box testing and User Acceptance Testing (UAT) show that the system functionality runs well and in accordance with user needs.